Single-site mutations in the conserved alternating-arginine region affect ionic channels formed by CryIAa, a Bacillus thuringiensis toxin. - Schwartz, J L (1997)
The role of the third domain of CryIAa, a Bacillus thuringiensis insecticidal toxin, in toxin-induced membrane permeabilization in a receptor-free environment was investigated. Planar lipid bilayer experiments were conducted with the parental toxin and five proteins obtained by site-directed mutagenesis in block 4, an arginine-rich, highly conserved region of the protein. Four mutants were constructed by replacing the first arginine in position 21 by a lysine (R521K), a glutamine (R521Q), a histidine (R521H), or a glutamic acid (R521E). A fifth mutant was obtained by replacing the fourth arginine by a lysine (R527K). Like CryIAa, the mutants formed cation-selective channels. A limited but significant reduction in channel conductance was observed for all mutants except R521H. The effect was more dramatic for the voltage dependence of the channels formed by R521K and R521Q, which was reversed compared to that of the parental toxin. This study provides the first direct evidence of a functional role for domain III in membrane permeabilization. Our results suggest that residues of the positive arginine face of block 4 interact with domain I, the putative pore-forming region of CryIAa.